PENGARUH BUDAYA ORGANISASI MADRASAH TERHADAP KINERJA GURU DI MTS NEGERI 2 DELI SERDANG - Lili Raflika; Rangga Hasibuan; Gita Asyari; Abdul Fattah Nasution (MERDEKA : Jurnal Ilmiah Multidisiplin, 2026)
This study aims to analyze the effect of madrasa organizational culture on teacher performance at MTs N 2 Deli Serdang. The research employed a quantitative approach with a causal research design. The population consisted of all teachers at MTs N 2 Deli Serdang, and total sampling was applied, resulting in 45 teacher respondents. Data were collected using a closed-ended questionnaire with a five-point Likert scale measuring madrasa organizational culture and teacher performance. The research instruments were tested for validity and reliability, and all items were found to be valid and reliable. Data analysis was conducted using descriptive statistics and simple linear regression with the assistance of SPSS software. The results indicate that madrasa organizational culture has a positive and significant effect on teacher performance. The coefficient of determination showsW that madrasa organizational culture contributes 58.7% to teacher performance, while the remaining percentage is influenced by other factors outside the research model. These findings highlight that strengthening madrasa organizational culture plays a crucial role in improving teacher performance and ensuring sustainable educational quality.